Islamic Leadership And Maqasid As-Syariah: Reinvestigating The Dimensions Of Islamic Leadership Inventory (Ili) Via Content Analysis Procedures - Mahazan Abdul Mutalib @ Talib; Mohd Rumaizuddin Ghazali; Nurhafizah Mohd. Sukor; Khairunneezam Mohd Noor; Aishah, HS; Azdi, WRWMF; Yuseri, A; Rosmizi, ARM; Muhammad, H; Azhar, IRM; Rozita, A; Abdullah, AG; et al. (Int Organization Center Acad Research, 2024)
Indexed by WOS